The Extreme C Terminus of Shigella flexneri IpaB Is Required for Regulation of Type III Secretion, Needle Tip Composition, and Binding - Roehrich, A. Dorothea (American Society for Microbiology (ASM), 2010)
Type III secretion systems (T3SSs) are widely distributed virulence determinants of Gram-negative bacteria. They translocate bacterial proteins into host cells to manipulate them during infection. The Shigella T3SS consists of a cytoplasmic bulb, a transmembrane region, and a hollow needle protruding from the bacterial surface. The distal tip of mature, quiescent needles is composed of IpaD, which is topped by IpaB. Physical contact with host cells initiates secretion and leads to assembly of a pore, formed by IpaB and IpaC, in the host cell membrane, through which other virulence effector proteins may be translocated. IpaB is required for regulation of secretion and may be the host cell sensor. However, its mode of needle association is unknown. Here, we show that deletion of 3 or 9 residues at the C terminus of IpaB leads to fast constitutive secretion of late effectors, as observed in a ΔipaB strain. Like the ΔipaB mutant, mutants with C-terminal mutations also display hyperadhesion. However, unlike the ΔipaB mutant, they are still invasive and able to lyse the internalization vacuole with nearly wild-type efficiency. Finally, the mutant proteins show decreased association with needles and increased recruitment of IpaC. Taken together, these data support the notion that the state of the tip complex regulates secretion. We propose a model where the quiescent needle tip has an “off” conformation that turns “on” upon host cell contact. Our mutants may adopt a partially “on” conformation that activates secretion and is capable of recruiting some IpaC to insert pores into host cell membranes and allow invasion.